PERMASALAHAN PENDIDIKAN PADA ASPEK ONTOLOGI, EPISTEMOLOGI DAN AKSIOLOGI DALAM PERSPEKTIF FILSAFAT PENDIDIKAN HINDU - Ni Putu Dian Utami Dewi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
This paper discusses educational problems in the aspects of ontology, epistemology, and axiology. Hindu education philosophy is the application of Hindu philosophical concepts into Hindu education problems which is found in the real teaching learning process. Vice versa, the implementation of education can also provide ideas/input for the improvement of the Hindu philosophical concepts. Those concepts and applications influence each other and work together to enhance each other. The problems of educational ontology in the study of Hindu educational philosophy covers the definition and nature of education and learning according to the Hindu perspective. Epistemological problems of education according to the study of Hindu education philosophy including philosophical problems (goals, curriculum and materials of Hindu education), actual problems (methods, educators and students in Hindu education), supporting problems (facilities, infrastructure and approaches of Hindu education). The problem of educational axiology in the study of Hindu educational philosophy concerns the philosophy of value. The intended value according to the study of Hindu religious education is the value of the usefulness/benefit of knowledge. Insightfully to those problems in the three pillars of philosophy, the educators, policy makers and education observers will be able to answer challenges and support the establishment of Hindu education that is beneficial, especially for students and the young generation of Hindus.@font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0;@font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-469750017 -1073732485 9 0 511 0;p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Calibri",sans-serif; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;.MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-family:"Calibri",sans-serif; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;div.WordSection1 page:WordSection1;